The effectiveness of San Francisco Coffee’s sales promotion towards the patrons / Noryusnita Ramli - Ramli, Noryusnita (2014)
This quantitative research focuses on the awareness, acceptance, preference and buying intention of the patrons of San Francisco Coffee towards sales promotion activities done by the company. This research is addressed through four objectives -1) to identify the level of San Francisco Coffee patrons’ awareness towards the company’s sales promotion, 2) to uncover the factors that attract San Francisco Coffee patrons’ acceptance towards the company’s sales promotional. 3) to unravel San Francisco Coffee patrons preference towards company’s sales promotional, and 4) to determine how San Francisco Coffee patrons’ buying intention affected by the company’s sales promotional. Data for this entire research is gathered using a survey method, which involved 364 patrons where convenient sampling was applied. These findings were categorized according to the objectives. Firstly, most of the respondents are aware on the sales promotion through Facebook. Secondly, in terms of the factors that attract them the most are the color, creativity and the message of the advertisement itself. Next, the respondents preferred to get any promotional messages from the company through newspaper, Facebook and Twitter apart from any other media. Lastly, in terms of the persuasiveness of the sales promotion, the data showed that most of them feel persuaded towards the buy-one-free-one and price discount promotion done by the company. Consequently, the researcher observed that the patrons of San Francisco Coffee are satisfied with the sales promotion techniques in fulfilling and satisfying their needs that also resulted to the effect of sales promotion contributes to high awareness, acceptance, preference and buying intention towards the patrons.